A good night for ghosts - Osborne, Mary Pope.; Murdocca, Sal (New York : Random House, 2009)
Jack and Annie must travel back in time to New Orleans in 1915 to help a teenaged Louis Armstrong fulfill his destiny and become the "King of Jazz."
"A Merlin mission."
"A Stepping Stone book."
3.7
3-6
Keywords: Time travel -- Juvenile fiction; Magic -- Juvenile fiction; Armstrong, Louis, -- 1901-1971 -- Childhood and youth -- Juvenile fiction; Jazz -- Juvenile fiction; African Americans -- Juvenile fiction; Brothers and sisters -- Juvenile fiction; New Orleans (La.) -- History -- 20th century -- Juvenile fiction; Time travel -- Fiction; Magic -- Fiction; Armstrong, Louis, -- 1901-1971 -- Fiction; Jazz -- Fiction; African Americans -- Fiction; Brothers and sisters -- Fiction; New Orleans (La.) -- Fiction; Time travel -- Fiction; Magic -- Fiction; Armstrong, Louis, -- 1901-1971 -- Fiction; Jazz music -- Fiction; African Americans -- Fiction; Siblings -- Fiction; New Orleans (La.) -- History -- Fiction